Development and Evaluation of Orodispersible Films of Donepezil Hydrochloride Utilizing Banana Powder as a Natural Disintegrant: Research Article (Journal of Pharma Insights and Research, 2025)
Alzheimer's disease is a progressive neurodegenerative disorder characterized by a decline in cognitive function and memory, primarily managed through acetylcholinesterase inhibitors such as Donepezil Hydrochloride. A significant challenge in the long-term management of this condition is patient non-compliance, frequently exacerbated by dysphagia in the geriatric population. To address these challenges, this study investigates the formulation and characterization of Orodispersible Films (ODFs) of Donepezil Hydrochloride, designed to disintegrate rapidly in the oral cavity without the need for water. The films were fabricated via the solvent casting method, utilizing Hydroxypropyl Methylcellulose (HPMC E15) as the primary film-forming polymer and varying concentrations of banana powder as a novel, natural disintegrant. Polyethylene Glycol (PEG-400) served as a plasticizer to ensure adequate mechanical flexibility. The formulations were subjected to rigorous physicochemical evaluation, including thickness, folding endurance, surface pH, weight variation, and disintegration time, alongside in vitro drug release studies. The results indicated that increasing the concentration of banana powder significantly reduced the disintegration time to less than 40 seconds while maintaining robust mechanical properties. The optimized formulation (F12) exhibited a drug release profile exceeding 99% within 60 minutes. FTIR analysis confirmed the chemical compatibility between the drug and excipients, while DSC analysis suggested a molecular dispersion of the drug within the polymer matrix. This research concludes that banana powder can be used as a potent, biocompatible, and cost-effective alternative to synthetic disintegrants, for enhancing therapeutic adherence in neurodegenerative therapies